The Pancasila Rule of Law and Democratic Backsliding in Indonesia A Critical Legal Perspective - I Gede Sujana; I Gusti Ngurah Santika; I Jero Gede Adi Pratama; Sindi Glaudia Ntarung; I Nyoman Silpa Mahadana; Ni Ketut Nike Lusiana (CV. Tirta Pustaka Press, 2026)
This article examines the Pancasila-based rule of law in Indonesia within the context of democratic backsliding using a Critical Legal Studies (CLS) approach. Normatively, Pancasila offers a synthesis of legality, morality, social justice, and religious values. This study addresses the growing tension between the normative ideals of the Pancasila-based rule of law and contemporary patterns of democratic backsliding in Indonesia, particularly regarding judicial independence, executive dominance, and restrictions on civil liberties. The weakening of judicial independence, the expansion of executive power, and the restriction of civil liberties indicate patterns of democratic erosion. Furthermore, the interpretive flexibility of Pancasila enables its instrumentalization by political elites to legitimize policies that deviate from democratic principles. This study employs a qualitative normative-empirical approach using Critical Legal Studies (CLS), constitutional analysis, and critical interpretation of legal and political discourse related to democratic regression in Indonesia. The findings indicate that democratic backsliding in Indonesia is reinforced by the political instrumentalization of Pancasila, enabling legal justification for executive power expansion and restrictions on democratic freedoms despite constitutional commitments to justice and the rule of law. Therefore, a critical reconstruction is necessary to strengthen legal integrity and democratic governance.